KERJASAMA PEMERINTAH INDONESIA DENGAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) DALAM MENANGANI PENGUNGSI ASAL IRAN SURVIVE DI MAKASSAR - Siti Mei Sarah (2020)
This study discusses the background of the arrival of refugees from Iran survive in the city of Makassar. The focus of this research is on adaptation related to Iranian refugees surviving in Makassar City who for years have not received certainty to be processed to a third country, as well as the situation of the refugees while living in several Rundenim and several community houses whose existence must be considered by IOM and Makassar city government. Accommodation The accommodation of refugee refugees has been provided by IOM, where IOM is an international organization focused on dealing with refugee problems. Iranian refugees claim to leave their country because of the fear and insecurity they feel in their home country and fear the threat of persecution and discrimination, especially those directly related to identity, namely religion and minorities that are inseparable from the political context of the Iranian government. Some of the factors behind the refugees from Iran to Makassar because of limited facilities in some detention centers in Indonesia so that they spread to several regions in Indonesia, one of them is in Makassar City. The policy taken by the Mayor of Makassar in issuing a residence permit in Makassar based on the Memorandum of Understanding with IOM in 2015 was considered to have contributed to the increasing number of refugees in Makassar. Refugees from Iran live and adapt directly to the Makassar community. With refugee problems that are said to be in a state of survival or uncertain conditions without getting certainty from third party organizers they feel boredom and to experience excessive stress